Penggunaan Obat Tradisional oleh Penderita Diabetes Mellitus dan Faktor-faktor yang Berhubungan di Wilayah Kerja Puskesmas Rejosari Pekanbaru Tahun 2015 - Emy Leonita; Ariska Muliani (STIKes Hang Tuah Pekanbaru, 2015)
Diabetes mellitus is a disease that can result in death, the current Government of Indonesia urged the public to consume the drug made from traditional because given the low side effects one of which treatment of DM. Based on a recapitulation of recording data related to disease dm known the number of patients dm most highest in public health center rejosari that is as much as the 228. The purpose of whether there is a traditional use of drugs by patients with diabetes mellitus and factors in the work that is associated puskesmas rejosari pekanbaru 2015. Type of this research is quantitative analytic observational by using Cross-sectional design. Research conducted in April to June 2015 in the region of clinics Rejosari Pekanbaru. The entire population is type II DM patients who live in the area of public health, the number of samples as much as Rejosari 150 people, sampling by taking note of the sufferer starts from the time closest to you, with the use of computerized data processing and analysis done in a univariate and bivariat with chi square statistical tests.The research results obtained as many as 78 people ( 52.0 % ) have used traditional and medical cures. Variable are associated with the use of medical drugs and is the education and traditional (CI=1,3-5,1), self motivation (CI=1,6-6,7), income P value = (CI=1,4-5,4), and cultural P value=0.016 , (CI=1,2-4,5).Is expected to puskesmas rejosari pekanbaru to hold the program BATRA , provided information about the type of traditional medicines appropriate for the treatment of DM, give testimony infirmasi by using people who use traditional medicine and medical.